Matrifocalidad y marginación en la periferia de San Cristóbal de las Casas (Chiapas, México)1 - Sánchiz Ochoa, Pilar (Revista Española de Antropología Americana, 2003)
The Mexican state of Chiapas —whose troubled sociopolitical and economic situation triggered the 1994 Zapatista uprising— has witnessed a massive displacement of indigenous populations during the last few years. An outcome of regional movement of people has been the appearance of new colonies in the outskirts of the town of San Cristobal de las Casas, especially those formed around the matrifocal family units. For the women in these shanty towns, life in the city has meant loss of family protection, isolation and the development of new survival strategies.